Demand for Family Planning among Poor Women in Uganda: Analysis of the Uganda Demographic and Health Surveys - Kabagenyi, Allen; Kakande, Pamela; Owayezu, Vianney (Research Square, 2020)
Family planning is one of the major cost-effective interventions to improve maternal health, reduce maternal and child mortality, and prevent unplanned pregnancies, yet its use remains low in sub- Saharan Africa, especially among the poor. In Uganda, little is known about the factors influencing the demand for family planning among the poor. This study examines the determinants of demand for family planning among poor women in a low income country. Methods: The study is based on data from the 2006, 2011, and 2016 Uganda Demographic and Health Surveys (UDHS). The analysis was carried using weighted samples of 2,238 in 2006, 2,164 in 2011, and 4,370 in 2016. Descriptive statistics, and binary logistic regressions presenting both the unadjusted and adjusted were used to examine the influence of different demographic, behavioral, and socioeconomic factors on poor women’s demand for family planning. Results: Our findings showed demand for family planning was 56% in 2006, 60% in 2011, and 65% in 2016 among women in the poorest and poorer household health quintiles who were married or in union. In all three surveys, women age 25-39 had higher odds of demand for family planning compared with women age 15-24 (AOR=1.5, 95% CI=1.1-1.9 in 2006, AOR=2.2, 95% CI=1.7-2.7 in 2011, AOR=1.7, 95% CI=1.5-2.0 in 2016). Women with no education had lower odds of demand for family planning compared with those with secondary education (AOR=0.4, 95% CI=0.3-0.6, pooled results). Also, in the 2011 UDHS, women who had heard about family planning on the radio had higher odds of demand (AOR=1.4, 95% CI=1.1-1.7, pooled) for family planning compared with those who had not, and in the 2006 survey women who had discussed family planning at a health facility had higher odds of demand for family planning (AOR=1.0, 95% CI=0.8-1.2) compared with women who had not done so. Conclusions: Demand for family planning is influenced by a woman’s age, educational attainment, religion, exposure to family planning messages on the radio, and discussion on family planning at a health facility. This study underscores the need for increased family planning counseling by health workers and more discussion about family planning at the health facility. The findings further suggest the need to provide increased adequate family planning services and information for the poor, uneducated, and rural women to meet the demand for family planning.
Keywords: DHS; Demand for family planning; Poor women; Uganda